Exploring teacher's role as motivators and role models in cultivating children's safe behavior: a qualitative study - Rahmah, Hani Auliya; Mahfuzah, Mahfuzah; Julaikah, Julaikah; Rofiatun, Rofiatun; Tursilowati, Sri Yuni (Jurnal Cakrawala Promkes, 2025)
Children are vulnerable to injuries and accidents in school environments due to cognitive limitations. Teachers play a crucial role in shaping children's safe behavior by transferring knowledge and acting as motivators and role models. This study aims to explore how teachers influence children's safe behavior using a qualitative descriptive approach. Data was collected through observations and focus group discussions (FGDs) and analyzed using thematic analysis. Findings indicate that 67% of children's behavior at school was categorized as safe, while 33% was unsafe. Observations were conducted across the play area, learning spaces, and the street in front of the school. Teachers have actively encouraged safe behavior by providing support and motivation. However, some students continue engaging in unsafe practices despite these efforts. Teachers also attempt to model safe behavior, such as walking calmly in hallways and sitting properly in classrooms. However, FGD findings revealed that half of the teachers did not fully practice safe behavior, notably by failing to wear helmets when riding motorcycles to school. In conclusion, teachers at SD Negeri Krajan have effectively acted as motivators, encouraging students to adopt safe behavior. However, their role as role models remains inconsistent, highlighting the need for greater self-adherence to safety practices. Strengthening teachers' commitment to modeling safe behavior could enhance the effectiveness of safety education in schools.